'The imagined ecologies of Mary Robinson: or how to see what isn't really there'. Issue 2 (4th May 2022) - Banner, Jessica
ABSTRACT: Success and celebrity status for eighteenth-century performers – especially female performers – have typically been conceptualized in terms of perceived appearance. Instead of possessing some inherent natural quality or "it factor" that constituted "celebrity, " recent discussions in eighteenth-century performance studies have suggested that to varying degrees actresses of the period acted as "authors" fashioning their own character personas through a myriad of public and private performances. This paper seeks to expand the ways in which researchers engage with eighteenth-century female performers in the archive, extending notions of authorship beyond the strictly textual domain. In dialogue with the existing foundation of literary scholarship this paper proposes examining eighteenth-century actress Mary Robinson's social and stage presence through an "imagined ecological" framework in order to delve into one specific instance of self-fashioning – her opera box at the King's Theatre during the 1782-3 season. Drawing upon material culture studies on the one hand, and literary documents on the other, this essay aims to reconstruct the optics of Robinson's celebrity in such a way that the textual evidence is not privileged at the cost of what lies in the margins.